Amino Acids in New Organic Fertilizer AnchoisFert. Issue 47 (14th December 2022) - Pagliaro, Mario; Lino, Claudia; Pizzone, Daniela Maria; Mauriello, Francesco; Russo, Mariateresa; Muscolo, Adele; Ciriminna, Rosaria; Avellone, Giuseppe
Abstract: The analysis via GC‐MS of the amino acids present in AnchoisFert, a new organic fertilizer co‐product of fish oil extraction from anchovy fillet leftovers using limonene, unveils the presence of 16 amino acids, essential, quasi‐essential and non‐essential. Leucine, glycine, glutamic acid and alanine are the most abundant AAs. Proline, aspartic acid, arginine, serine, lysine and phenylalanine are also relatively plentiful. Alongside the results of the techno‐economic and life cycle assessment analyses, these outcomes suggest that the "LimoFish" circular economy process is highly effective in recovering valued AAs that otherwise would be lost in the environment. This greatly improves the sustainability of anchovy fishing, processing and consumption, further supporting the scale‐up and industrialization of the process. Abstract : The proteins of AnchoisFert, the organic fertilizer co‐product of anchovy fillet leftovers extraction with limonene, include 16 amino acids, essential, quasi‐essential and non‐essential. The LimoFish circular economy process is highly effective in recovering valued AAs that otherwise would be lost in the environment, improving the overall sustainability of anchovy fishing, processing and consumption.